By His mercy : an autobiography of Dr Ebenezer Oluyemi Babatunde - Babatunde, Ebenezer O.; Babatunde, Ebenezer O. (Ibadan: Christ and We)
An autobiography of Dr. E.O Babatunde, a renowned Obstetrician and Gynaecologist, an educationist and a philanthropist per excellence. The Founder of First Mercy Hospital, Akure.
oej 20/11/2019
Loans
Keywords: Babatunde, Ebenezer O; Autobiography; Nigeria